2015
DOI: 10.4238/2015.june.26.13
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of bone marrow mesenchymal stem cells on T lymphocytes in patients with decompensated liver cirrhosis

Abstract: ABSTRACT. We explored the immunomodulatory effects of bone marrow mesenchymal stem cells (BMSCs) on peripheral blood T lymphocytes in patients with decompensation stage, hepatitis B-associated cirrhosis. MSCs from nine patients were analyzed by flow cytometry. Peripheral blood lymphocytes were isolated for fluorescent staining. Following stimulation by phytohemagglutinin (PHA), peripheral blood lymphocytes were co-cultured with BMSCs in serum and divided into four groups: (1) BMSC + lymphocyte + PHA contact cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The live cells were counted using trypan blue solution % 0.04. The cell viability and the cell numbers were more than 98 % and 2.5×10 6 cells/mL, respectively in all samples (Guo et al, 2015[ 26 ], Askari et al, 2016[ 10 ]). The proliferation of isolated lymphocytes was assessed using colorimetric WST-1 assay kit (Roche Diagnostic, Mannheim, Germany) according to manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…The live cells were counted using trypan blue solution % 0.04. The cell viability and the cell numbers were more than 98 % and 2.5×10 6 cells/mL, respectively in all samples (Guo et al, 2015[ 26 ], Askari et al, 2016[ 10 ]). The proliferation of isolated lymphocytes was assessed using colorimetric WST-1 assay kit (Roche Diagnostic, Mannheim, Germany) according to manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 95%
“…Fifteen ml of brachial vein whole blood were prepared from each subject and collected into a heparinized tube. Peripheral blood mononuclear cells (PBMC) were separated using Ficoll density gradient as described previously (Boskabady et al, 2011[ 19 ]; Guo et al, 2015[ 26 ]; Askari et al; 2018[ 8 ][ 9 ]). The live cells were counted using trypan blue solution % 0.04.…”
Section: Methodsmentioning
confidence: 99%
“…BMSCs secrete various soluble mediators, inhibit the proliferation and activation of various immune cells, and ultimately inhibit the activation of hepatic stellate cells. Research by Guo et al found that MSCs transplantation in patients with liver cirrhosis can inhibit the proliferation of peripheral blood T lymphocytes, upregulate the expression of CD4, CD25, and CD127, regulatory T cells (Treg), and also alleviate the Treg/Th17 imbalance [ 16 ]. Liu et al [ 17 ] also found that, during liver fibrosis, CD4+, CD25+, FoxD3, and other regulatory T cells in the liver increased, while NK cells decreased.…”
Section: Mechanism Of Bmscs In Liver Cirrhosismentioning
confidence: 99%
“…BMSC-derived exosomes are nano-sized extracellular vesicles loaded with various RNAs and proteins, and act as paracrine factors in intercellular communication[8] [9]. Exosome-based therapy is an emerging modality in various in ammatory conditions involving an overactive immune system [10] [11], and has shown promising effects in clinical trials and experimental models [12]. Several studies have demonstrated that the modulation of regulatory T cells (Tregs) is due to immunoregulatory effects of exosomes [13] [14].…”
Section: Introductionmentioning
confidence: 99%